Meningkatkan Keterampilan Berbicara Siswa melalui Model Pembelajaran Everyone is a Teacher Here Kelas 4 SDN 14/I Sungai Baung - Parastu, Rekhano Andria; Arista, Reni; Pramulia, Fuji; Pribadi, Chiquita Azura; Destrinelli, Destrinelli (Lembaga Yasin AlSys, 2023)
Speaking skills are one of the important components that must be possessed in students wherever they are. With these speaking skills students can be skilled at speaking by training and demanding students to be able to communicate with friends and the surrounding environment. In addition, with speaking skills students can express, state and convey ideas, thoughts, ideas, or feelings to others. This type of research is classroom action research (CAR). This research was conducted with an effort to improve students' speaking skills through the Everyone Is A Teacher Here learning model for class 4 SDN 14/I Sungai Baung TP. 2022/2023. This study uses observation and documentation techniques. The research process went through two stages, namely cycle I and cycle II. Through four stages, namely planning, implementation, evaluation, and reflection. The results of observations in the first cycle became a reference for improvement in the next cycle. The reflection phase refers to cycle I, the expected goals have not been achieved. Cycle II is an improvement from cycle I which was previously implemented. The deficiencies that existed in cycle I were corrected in cycle II. Cycle II was prepared and planned more carefully for student learning outcomes and behavior. Based on the discussion of students' ability in speaking skills through the Everyone Is A Teacher Here method, it was concluded: 1. The average result of cycle I was 80.1 and cycle II was 82.3 increased by 2.2. 2. The learning outcomes in cycle I achieved classical completeness of 80.9% and in cycle II it became 100%. 3. Student activity in cycle I was 56% and cycle II was 87%.